The professional profile of the data journalist in Peru: Case studies of Ojo Público, Convoca, El Comercio Data and La República Data - Romero Benites, Rocío Lizbetty (2022)
This research describes the professional profile of journalists who work in newsrooms that are pioneers in data analysis in Peru: Ojo Público and Convoca, as native digital media, and El Comercio Data and La República Data, as part of traditional media. To achieve this objective, and through a mixed approach, their bosses, coordinators or directors are interviewed, and questionnaires are applied to the journalists who work in them. The results show that journalists follow the methodology of data journalism, consisting of seven work phases: compile, clean, context, combine, analysis, verification and communication of data, and using technological tools in each of them with a skill level that is primarily not expert. In addition, most of their knowledge was self-taught, thus evidencing a lack of specialization in data journalism in the Peruvian higher education.